An efficient synthesis of triazolium ion based NHC precursors using diaryliodonium salts and their photophysical properties. Issue 40 (1st October 2018) - Pilania, Meenakshi; Rohman, Mostofa Ataur; Arun, V.; Mehra, Manish Kumar; Mitra, Sivaprasad; Kumar, Dalip
Abstract : Triazolium salts were prepared by copper-catalyzed N -arylation of fused triazoles using diaryliodonium salts. These salts could behave as versatile NHC catalysts and fluorescent probes. Abstract : Copper-catalysed N -arylation of fused triazoles using diaryliodonium salts as an aryl source is described. This scalable protocol displayed good compatibility towards diverse sensitive functional groups like ester, alkyl and nitro groups and halogens (F, Cl, Br). The synthetic usefulness of the prepared triazolium salts was proved by preparing α-hydroxyketone through benzoin condensation. Photophysical studies of these compounds showed promising Stokes-shifted fluorescence emission in aqueous medium, so this molecular framework could be a proficient probe for biological applications.